Resource innovations in market conditions - Strunin, Viktor (My University, 2014)
Nowadays resource innovations are the one of powerful instruments to reach leadership and positions of success at local market and at branch at all. This forces enterprises to find a proper way at business strategy and involves different managerial actions to create a base point to start innovation process at this path.
Keywords: ресурсні інновації; resource innovation; кафедра економіки праці та менеджменту